2006
DOI: 10.3390/11010103
|View full text |Cite
|
Sign up to set email alerts
|

Screening Analyses of Pinosylvin Stilbenes, Resin Acids and Lignans in Norwegian Conifers

Abstract: Abstract:The content and distribution of stilbenes and resin acids in Scots pine (Pinus sylvestris) and spruce (Picea abies), sampled in central Norway, have been examined. The contents of pinosylvin stilbenes in pine heartwood/living knots were 0.2-2/2-8 % (w/w). No stilbenes could be detected in spruce (Picea abies). The resin acid contents of pine sapwood/heartwood and knots were 1-4 and 5-10 % (w/w), respectively. Minor amounts of resin acids (<0.2/<0.04 %w/w) were identified in spruce wood/knots. The lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 22 publications
5
76
0
2
Order By: Relevance
“…Increased amounts of stilbenes in knotwood compared to stemwood have been reported for Pinus sylvestris (Willför et al 2003a) and Pinus radiata (Hillis and Inoue 1968;Pietarinen et al 2006a). Mass ratios of pinosylvin monomethyl ether/pinosylvin in the range 1.1 to 1.4 (near the values determined in this work) have been reported for Pinus sylvestris (Hovelstad et al 2006).…”
Section: Water-soluble Saccharidessupporting
confidence: 60%
See 1 more Smart Citation
“…Increased amounts of stilbenes in knotwood compared to stemwood have been reported for Pinus sylvestris (Willför et al 2003a) and Pinus radiata (Hillis and Inoue 1968;Pietarinen et al 2006a). Mass ratios of pinosylvin monomethyl ether/pinosylvin in the range 1.1 to 1.4 (near the values determined in this work) have been reported for Pinus sylvestris (Hovelstad et al 2006).…”
Section: Water-soluble Saccharidessupporting
confidence: 60%
“…Studies have reported the occurrence and the extraction of pinosylvins from conifers such as Picea abies, Pinus sylvestris (Willför et al 2003a(Willför et al , 2003bPietarinen et al 2006a;Hovelstad et al 2006), Pinus thunbergii (Kokubo et al 1990), Pinus strobus (Geraldo de Carvalho et al 1996), Pinus radiata (Hillis and Inoue 1968), Pinus contorta (Loman 1970), Pinus sibirica, and Pinus cembra (Willför et al 2003c). The occurrence of pinosylvins has also been reported for Pinus jeffreyi (Anderson 1956), Pinus resinosa (Simard et al 2008), and Pinus griffithii (Mahesh and Seshadri 1954).…”
Section: Water-soluble Saccharidesmentioning
confidence: 99%
“…Previous studies reported that reaction zones in Picea abies wood, the formation of which was induced by the fungus Fomes annosus, contained a significantly increased concentration of hydroxymatairesinol (up to 6% of the total dry mass fraction), whereas the sound sapwood contained negligible amounts of the lignan compounds (Hovelstad et al 2006;Shain and Hillis 1971). At least a small part of brown stained phenolic compounds that occur in the necrotic rays of Picea abies wood may be related to lignans (Johansson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Lipids in lignocellulose comprise a wide range of different compounds including fatty acids, glycerides, sterols and waxes [45]. Terpenoids such as monoterpenes and diterpenes can be found in softwood residues [46,47] and triterpenes are constituents of hardwood bark [48]. Polyphenols are found in softwood and hardwood and are represented by a wide range of compounds including gallotannins and ellagitannins, proanthocyanidins, flavonoids, lignans and stilbenes [49][50][51].…”
Section: Composition and Treatment Of Lignocellulose Materialsmentioning
confidence: 99%